EFFECT OF COVID-19 INFECTION ON PREGNANCY-INDUCE HYPERCOAGULABILITY: ВЛИЯНИЕ ИНФЕКЦИИ COVID-19 НА ГИПЕРКОАГУЛЯЦИЮ, ВЫЗВАННУЮ БЕРЕМЕННОСТЬЮ - Z. ZAALISHVILI; N. PKHALADZE (Experimental and Clinical Medicine Georgia, 2021)
COVID-19 is one of the most wide-spread pandemics in more than 100 years. At the time of writing this case report (Dec 19, 2020), there has already been a total of 75.5 million cases and 1.6 million deaths since the onset of the pandemic [3,6,7]. Although we have a good understanding of how various comorbidities affect the outcome of COVID-19 patients, we have less data about the clinical course of COVID-19 in pregnant patients [4,5]. One of the most significant aspect of pregnancy and concomitant COVID-19 is the risk of hypercoagulable complications in the patient [4,10]. Pregnant women are already at high risk of thrombotic conditions due to physiologic changes in pregnancy and COVID-19 has also been shown to exacerbate hypercoagulability [8,9]. Here we report the case series about 7 patients with significant laboratory derangement possibly indicating worsening hypercoagulability. We believe that correlation between pregnancy and COVID-19 induced hypercoagulability will give rise to many further questions and the answers from the medical society will likely prevent many cases of life-threatening thrombotic complications in pregnant women across the world.